The Pandemic Paradox : Unfolding the Impact Of COVID-19 Twin Crises on Domestic Violence in Malaysia - Shirly Wong Siew, Ling; Chew, Keng Sheng; Cheah, Joe Seng; Siew, Ke Lin (2022)
The coronavirus 2019 (COVID-19) pandemic is truly a stunning global experience that deepened economic, social, and health-related disparities, mercilessly pushing all aspects of livelihood into vulnerability state. The scale of the COVID-19 impact is more than just a health crisis or economic crisis. When the virus sail through the territory, health containment measures necessary to reduce the speed of virus transmission such as social isolation, mandatory quarantines, border closures, school closures and working from home have worsened personal and collective vulnerabilities, resulting in unintended consequences on domestic violence. The upsurge of family victimization has enormously affected those who were already most likely to experience disaster-related instability, steep losses in employment, economic stress as well as those who are living in exploitative relationships and ill health. In view of this, the recovery of the nation is surrounded by a trio of interlocking crises that worth empirical investigation. Using panel analysis on family violence data extracted from the Royal Malaysia Police (RMP), the study uncovered the presence of worsened the structural factors in the society that contribute to the escalating domestic violence in Malaysia.